Investigation into applicability and efficiency of SQLite for implementation of Dijkstra's algorithm - Yurchak, Iryna; Dudas, Volodymyr (2017 14th International Conference The Experience of Designing and Application of CAD Systems in Microelectronics (CADSM), 2017)
The work presents the results of comparison of tools for implementing an algorithm for calculation of the shortest path in a graph in mobile applications. We've revealed the amount of nodes starting from which Dijkstra's algorithm implementation in Java fails or at best becomes inferior to SQL implementation of the same algorithm. The results of the performed investigations come in useful for managers of mobile applications projects when taking decision on the architecture of the application being developed under assumption that the application assumes seeking for the best route and the amount of nodes in a graph representing road network is known in advance.